2019
DOI: 10.1101/19004960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of host-pathogen-disease relationships using a scalable Multiplex Serology platform in UK Biobank

Abstract: Background: Certain infectious agents are recognised causes of cancer and potentially other chronic diseases. Identifying associations and understanding pathological mechanisms involving infectious agents and subsequent chronic disease risk will be possible through measuring exposure to multiple infectious agents in large-scale prospective cohorts such as UK Biobank. Methods: Following expert consensus we designed a Multiplex Serology platform capable of simultaneously measuring quantitative antibody responses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 69 publications
6
29
1
Order By: Relevance
“…In contrast, our study demonstrated consistently higher EBV seroprevalence among all age brackets compared to a comparable older study [18] this may reflect a genuine increase in seroprevalence in the UK, differences in population sampling, or different sensitivity and specificity of the assays used (our study used VCA whereas previous studies have used EBNA). Reassuringly, our estimates closely mirror those from a recent random sampling of UK Biobank participants: among those aged 40-69 years, EBV seroprevalence was 94.7% 1 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, our study demonstrated consistently higher EBV seroprevalence among all age brackets compared to a comparable older study [18] this may reflect a genuine increase in seroprevalence in the UK, differences in population sampling, or different sensitivity and specificity of the assays used (our study used VCA whereas previous studies have used EBNA). Reassuringly, our estimates closely mirror those from a recent random sampling of UK Biobank participants: among those aged 40-69 years, EBV seroprevalence was 94.7% 1 .…”
Section: Discussionsupporting
confidence: 80%
“…Epstein-Barr Virus (EBV) is a ubiquitous gammaherpesvirus with which~95% of healthy adults are infected [1]. EBV is the commonest causative agent of Infectious Mononucleosis (IM), a triad of pharyngitis, lymphadenopathy and fever in the context of acute EBV infection [2].…”
Section: Introductionmentioning
confidence: 99%
“…The full study population consisted of a randomly drawn subset of 9695 individuals from the UK Biobank cohort [ 32 , 36 ]. UK Biobank obtained ethics approval from the Research Ethics Committee (REC; approval number: 11/NW/0382) and informed consent from all participants enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded variants out of Hardy-Weinberg equilibrium at p<1´10 -5 , call rate <95% (alternate allele dosage within 0.1 of the nearest hard call to be non-missing), imputation quality INFO<0.30, and MAF<0.01. Seropositivity for each antigen was determined using established cut-offs based on prior validation work 15 .…”
Section: Genome-wide Association Analysismentioning
confidence: 99%
“…High levels of specific IgG's can be the result of chronic infection, while low levels may indicate poor immunity. Viruses assayed in the UKB multiplex serology panel were previously chosen based on putative links to chronic diseases including cancer, autoimmune, and neurodegenerative conditions 15 .…”
Section: Introductionmentioning
confidence: 99%